STRATEGI POSTER SESSION DALAM MENINGKATKAN PEMAHAMAN SISWA DALAM PEMBELAJARAN FIQIH - Irwandi (FITRAH: International Islamic Education Journal, 2020)
The problems that exist in students' understanding of Fiqh learning in class V MIN Rukoh Banda Aceh. Learning that is only carried out by the lecture method makes students less enthusiastic about participating in learning and makes students less interact with teachers and other students. This causes student understanding is still lacking. The data collection techniques used were written test results and observations. The research used is Classroom Action Research, which consists of four stages including planning, implementing, observing and reflecting. The purpose of this study was to determine the ability of students to understand Islamic Islamic Civilization History learning before using the Poster Session strategy, to know the learning process using the Poster Session strategy, and to find out the students' understanding ability after using the Poster Session strategy. Based on the results of the study, in the pre-cycle the students' understanding ability was still below the KKM, with an average of 53%. After using the Poster Session strategy in the first cycle, the results of student activity observations increased by 65%. Whereas in cycle II the results of student observations reached 82%. The results of students' understanding ability after the implementation of the Poster Session strategy have increased in each cycle. In the first cycle, the students 'learning completeness was 50.15%, while in the second cycle, the students' learning completeness increased to 85%.